2011
DOI: 10.1007/s13165-011-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter pools and crop yields as affected by the rate of farmyard manure and use of biodynamic preparations in a sandy soil

Abstract: One aim of organic and biodynamic agriculture is to improve soil fertility. Our objectives are to (1) explain previously reported differences in the soil organic matter levels between soils receiving farmyard manure (FYM) with or without biodynamic preparations (BD), (2) quantify the effect of three levels of FYM applications on microbial biomass and soil organic matter (SOM) pools with different stability, and (3) relate SOM pools to crop yields in a long-term experiment on a sandy soil at Darmstadt, Germany.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Similarly, the highest increase in TOC and TON from compost than other amendments in our study was due to its dual effect by directly contributing to organic C and N, plus additional indirect contri ution of C from increased b crop residue (roots, stubble, straw, chaff/fallen leaves) returned to the land/soil, as evidenced by greatest increase in straw yield in this treatment [39]. Inorganic amendments usually supply specific nutrients and do not contribute directly to soil organic matter, resulting in much less contribution to soil organic C and N. Other recent research in Germany has also shown significant increase in soil organic matter after four annual applications of farm yard manure (FYM) to organic crops [7]. The relative greater increases in C or N for LFOC or LFON than TOC or TON in our study are in agreement with other research, where light organic fraction was also more responsive to management practices than total organic fraction [14][15][16].…”
Section: Soil Organic C and Nmentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly, the highest increase in TOC and TON from compost than other amendments in our study was due to its dual effect by directly contributing to organic C and N, plus additional indirect contri ution of C from increased b crop residue (roots, stubble, straw, chaff/fallen leaves) returned to the land/soil, as evidenced by greatest increase in straw yield in this treatment [39]. Inorganic amendments usually supply specific nutrients and do not contribute directly to soil organic matter, resulting in much less contribution to soil organic C and N. Other recent research in Germany has also shown significant increase in soil organic matter after four annual applications of farm yard manure (FYM) to organic crops [7]. The relative greater increases in C or N for LFOC or LFON than TOC or TON in our study are in agreement with other research, where light organic fraction was also more responsive to management practices than total organic fraction [14][15][16].…”
Section: Soil Organic C and Nmentioning
confidence: 74%
“…In a growth chamber study, Qian et al [8] showed significant increase in total N in soil with application of alfalfa powder and anticipated increase in N availability to subsequent crops. In a field study in Germany, Heitkamp et al [7] found significant increase in labile N with application of FYM for four years, and the increase was strongly related to rate of FYM and also to crop yield. In another study in southern Alberta, Canada, long-term applications of cattle manure increased potentially mineralizable N and P in soil samples collected every five years over 25-year period [40].…”
Section: Soil Organic C and Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter is the primary source of many nutrients in organic farming systems (Heitkamop et al, 2011). Retention of organic matter is essential for good management and provides other benefits to soil conditions for www.ccsenet.org/sar Sustainable Agriculture Research Vol.…”
Section: Examples Of Sources Of Nutrients From Organic Mattermentioning
confidence: 99%
“…Furthermore, the avoidance of loss of nutients into the surrounding environment, including loss to groundwater, is also a high priority for organic systems (Askegaard et al, 2011). The effectiveness of use of nutrients in organic farming systems depends on the rate of cycling of nutrients from both organic matter and allowable minerals, which differ in magnitude according to the soil's inherent fertility (Heitkamop et al, 2011) and mineralogical composition (van Straaten, 2002). Globally, soils used for organic agriculture range from deep, highly fertile soils to shallow, highly weathered and nutrient depleted soils (Chivenge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%